AB0984 Herpes Zoster Vaccination, Should Our Patients with Rheumatological Disorders Be Prioritized?. (15th July 2016) - Khan, A.; Roopa, T.; Williamson, L.; Collins, D.; Price, E.; Ahmed, A.; Carty, S.
Abstract : Background: Herpes Zoster infection is a common and painful condition with potential for serious complications. The overall life time risk is one in three but the risk is much higher in immunosuppressed patients and in our patients with rheumatological diseases. For example in patients with rheumatoid arthritis alone the risk is 2 fold higher compared to the age and sex matched controls. The risk also increases with age and more than 50% of Herpes infection occurs in those aged over 60. The Herpes Zoster vaccination has been approved by FDA for people aged 50 years and older and CDC recommends it in those aged 60 and above. In United Kingdom this vaccination has recently been started, last year only people who were 70 and 79 years old were being offered the vaccine and this year those aged 71 and 78 are being vaccinated. Current guidelines do not recommend vaccination on biologic treatment, high dose steroid or other significant immunosuppression. Objectives: This is a small study to look into Herpes infection in our rheumatology patients and whether we need a more pro-active approach towards vaccinating our patients particularly those who are about to start biologic therapies. Methods: We looked at the self-reported incidence of Herpes Zoster infection in our cohort of rheumatology patients. We sent out a questionnaire to all patients on our biologics database asking if they had ever suffered from shingles and whether they had it before or after their respective rheumatological diagnosis and if they were on a biologic or non-biologic DMARD at the time of shingles. Of 512 sent, 160 replied. Mean Age was (65) and main rheumatological diagnoses were: Rheumatoid Arthritis 96/160 (60%), Psoriatic Arthritis 29/160 (18%), and Ankylosing spondylitis 21/160 (13%), the rest were other conditions treated with biologics. Results: 38 of 160 (23.75%) had previous shingles and 6 of these 38 patients (15.7%) had suffered more than one episode. 24 of 38 (63.1%) patients had shingles post rheumatologic diagnosis and out of these 24; 6 (25.0%) had shingles whilst on biologic treatment; 6 (25.0%) had it whilst on combination DMARDs plus biologics; 9 (37.5%) on small molecule DMARDS; 3 patients could not tell their drugs at the time of shingles. The mean age for those who had shingles was 61.8 years. Conclusions: Nearly one quarter of patients on our biologic database reported one or more episodes of shingles. Out of them 63% had it post their rheumatological diagnosis, and most patients had it whilst on Biologic or Non-Biologic DMARDs. The mean age of those who had shingles was 61.8 years which is much less than the current cut off for vaccination in UK. This is a small study but serves as a reminder for us to consider a more proactive approach towards shingles vaccination in our rheumatology patients, particularly before starting Biologics, in older patients who do not qualify for routine government funded Vaccination. References: Allison L. Smitten, Hyon K. Choi, Marc C. Hochenberg, Samy Suissa, Teresa A. Simon, Marcia A. Testa, K. Arnold Chan. The risk of herpes zoster infection in patients with rheumatoid arthritis in United States and United Kingdom. 29 Nov 2007. DOI: 10. 1002/ART.23112. Craig M. Hales, MD, Rafael Harpaz, MD, Ismael Ortega-Sanches PhD, Stephanie R. Bialek, MD. Update on recommendations for use of Herpes Zoster Vaccine August 22, 2014/63(33);729–731 Disclosure of Interest: None declared